CircRNAs in lung cancer - Biogenesis, function and clinical implication. (1st November 2020) - Wang, Chengdi; Tan, Shuangyan; Li, Jingwei; Liu, Wen-Rong; Peng, Yong; Li, Weimin
Abstract: Lung cancer is the leading cause of malignancy-related incidence and mortality worldwide. Molecular mechanisms underlying tumorigenesis and development of lung cancer are still warranted to be elucidated. Previous studies have shown that non-coding RNAs are related to the tumorigenesis and progression of various cancers. However, the expression patterns and clinical implications of circRNAs in lung cancer remain obscure. CircRNAs are a special class of non-coding RNAs with stable covalently closed circular structures, high abundance and tissue/cell/development-specific expression patterns. Thus, circRNAs are a new frontier in lung cancer research. Therefore, in this review, we elucidated the biological function and mechanism of circRNAs, as well as the role of aberrant expressed circRNAs in proliferation, invasion, drug resistance and tumor microenvironment. Furthermore, we discussed that circRNAs may serve as potential clinical biomarkers for the diagnosis, prognosis and treatment of lung cancer.